Peran Kepuasan Kerja dan Komitmen Organisasi Memediasi Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan - Fery Panjaitan (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2022)
The purpose of this study was to explain the role of job satisfaction and organizational commitment to mediate the efffect of organizational culture on employee performance. The population of this research is the employees of PT. Indomarco Prismatama (Indomaret) Pangkalpinang, totaling 115 people. The analytical tool used is path analysis using SEM method (struktural equation modeling) using SmartPLS 3. The results of the study indicate that organizational culture had a positive and significant effect on satisfaction. Organizational culture has a positive and significant effect on employee performance and organizational culture also has a positive and significant effect on organizational commitment. Furthermore, job satisfaction has a positive and significant effect on employee performance and organizational commitment has a positive and significant effect on employee performance. Job satisfaction is able to partially mediate the influence of organizational culture on employee performance and organizational commitment is able to partially mediate the influence of organizational culture on employee performance. Therefore, it is important for leaders in the company to pay attention to and develop job satisfaction and organizational commitment so that organizational culture can improve employee performance.